Quantitative climatic reconstruction and prehistoric human subsistence strategy evolution since the mid-Holocene in Nenjiang river Basin, Northeastern China. (10th March 2023) - Leng, Chengcheng; Jie, Dongmei; Zhang, Can; Tang, Zhuowei; Sun, Xiaoshuang; Yan, Tianlong; Zhao, Cheng
Abstract: Quantitative paleoclimate reconstructions can provide crucial climate context to test the hypothesis of climatic impact on prehistoric human activities. However, the climate change in Nenjiang River Basin is poorly understood due to the lack of reliable paleoclimate records. In this study, we report paired quantitative temperature (MAAT0 ) and soil pH records based on the branched glycerol dialkyl glycerol tetraether (brGDGTs) since the mid-Holocene in an alluvial sedimentary sequence near the Honghe Neolithic site in the middle reaches of Nenjiang River Basin. The result of MAAT0 shows an obvious cooling interval at 6.5–4.0 kyr BP, which is consistent with paleotemperature reconstruction results in EASM margin. The strengthened westerlies may play a crucial role in shaping the cooling mid-Holocene in EASM margin. The soil pH variations yield a peak at 6.0–3.5 kyr BP, which is roughly consistent with other precipitation reconstruction from northeastern China. From the middle Neolithic to Bronze period, the prehistoric humans gradually settled in Nenjiang River Basin. Cool-wet climate during 6.0–4.0 kyr BP provide enough water & wildlife resources and broader space for human survival and thus prompted the settlement and cultivation development. With the deterioration of the climate since 4.0 kyr BP, the ancient inhabitants have to move southward along the Nenjiang River to lower reaches to find more suitable places for settlement.